2006
DOI: 10.1191/0960327106het645oa
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Myocardial Damage in 83 Young Adults with Carbon Monoxide Poisoning in the East Anatolia Region in Turkey

Abstract: Carbon monoxide (CO) poisoning is the leading cause of death from intoxication. In CO poisoning, it is important to know if there are any symptoms regarding myocardial damage, which are usually unobserved as a result of hypoxia. This study was planned to assess myocardial damage in young healthy patients with CO poisoning. Eighty-three young healthy cases who had been exposed to CO were included in this study. The demographic and clinical characteristics, the origin of CO gas and smoking habits of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 25 publications
1
40
0
Order By: Relevance
“…As the most common cause of death from poisoning worldwide, cardiovascular manifestations of acute CO poisoning have been the subject of various studies, but current evidence about the effects of chronic CO exposure on the cardiovascular system is limited (Ernst et al, 1998;Satran et al, 2005;Kalay et al, 2007; Davutoglu et al, 2006;Aslan et al, 2006). As chronic exposure to CO without acute toxicity is common in the environment and in some professions, unveiling this interaction is very important.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As the most common cause of death from poisoning worldwide, cardiovascular manifestations of acute CO poisoning have been the subject of various studies, but current evidence about the effects of chronic CO exposure on the cardiovascular system is limited (Ernst et al, 1998;Satran et al, 2005;Kalay et al, 2007; Davutoglu et al, 2006;Aslan et al, 2006). As chronic exposure to CO without acute toxicity is common in the environment and in some professions, unveiling this interaction is very important.…”
Section: Discussionmentioning
confidence: 98%
“…Cardiovascular manifestations of acute CO poisoning include myocardial dysfunction, ischemia, infarction, arrhythmias, and cardiac arrest, which have been the subject of various studies (Ernst et al, 1998;Satran et al, 2005;Kalay et al, 2007;Davutoglu et al, 2006;Aslan et al, 2006, Yildirim et al, 2005Wellenius et al, 2006). However, our knowledge about the effects of chronic CO exposure on cardiovascular system is limited.…”
mentioning
confidence: 97%
“…Acute CO poisoning includes brain, heart and kidneys (2,6). Acute coronary syndrome, myocardial damage, dysfunction, ischemia, infarction, fibrosis, atrial thrombus, arrhythmias, and cardiac arrest are the cardiovascular changes reported in acute CO poisoning (1,3,(6)(7)(8)(9)(10)(11)(12)(13). Previous reports with small number of patients with acute CO poisoning indicated that in some of the cases; attacks of atrial fibrillation (AF), premature beats, episodes of sinus tachycardia and alterations in ventricular repolarization were observed (14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…These compounds turn soil and lakes acidic and corrode building structures [4]. High concentrations of CO in the atmosphere cause harmful effects to human health by reducing the oxygen levels in the blood vessel delivered to body organs and tissues [5]. Biodiesel is a mono alkyl ester of long fatty acids derived from renewable lipid feed stocks, such as vegetable oil and animal fats, for use in compression ignition diesel engines [6,7].…”
Section: Introductionmentioning
confidence: 99%